Regional Strategic Analysis and Knowledge Support System in Asia (ReSAKSS -Asia) - Regional Strategic Analysis and Knowledge Support System in Asia (ReSAKSS-Asia) (International Food Policy Research Institute, 2013)
Regional Strategic Analysis and Knowledge Support System in Asia (ReSAKSS-Asia) is an initiative based on a multi-country regional network for informing current and future food and nutrition security strategies in the Asia region. The overall goal of ReSAKSS-Asia is to help fill key knowledge gaps, promote policy dialogue and sharing of lessons and experience across countries in the region, and establish a web-site portal to provide easy access to key information and knowledge on issue related to agricultural growth and improved food security and nutritional outcomes in the Asia region.